Znaczenie orzecznictwa sądowego dla publicznego prawa gospodarczego - Kiczka, Karol (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The influence of judicial adjudication on public economic law has – for a long period of time – been a subject matter of different scientific texts. The legal doctrine is correct in seeing judicial adjudication as a substantive factor for the proper conduct of both adopting and applying public economic law. Tribunals and courts of law are the guarantors of the democratic state ruled by law in a social market economy. The significance of judicial adjudication for adopting and applying public economic law justifies the view that judicial pronouncements have the status of a secondary factor shaping legal order (a status of secondary, non-organized, non-formal sources of law).
Keywords: public economic law; judicial adjudication; democratic state ruled by law